Ineffective Sentence Construction in Descriptive Texts: A Linguistic Analysis of Eighth-Grade Students at Ibnu Utsman Boarding School Tanjungpinang - Indah Purmasari; Sujinah (International Journal of Technology and Education Research, 2025)
This study aims to analyze the forms of ineffective sentence construction found in descriptive texts written by eighth-grade students at Ibnu Utsman Boarding School Tanjungpinang. The research employs a descriptive qualitative method using a linguistic analysis approach applied to 22 descriptive texts as the primary data source. The findings indicate that the most dominant errors occur at the phrase level, including the influence of local languages, incorrect use of prepositions, and word arrangements that do not conform to grammatical rules. In addition, syntactic errors at the sentence level were also identified, particularly sentences lacking subjects. The factors contributing to these errors include mother-tongue interference, limited use of standard Indonesian in daily communication, and the students’ low interest in and limited practice of writing. These findings suggest the need for more structured writing instruction strategies, such as intensive practice, strengthening understanding of spelling conventions, and implementing contextual learning to enhance students’ written language proficiency.